1991
DOI: 10.1073/pnas.88.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy of a wheat seed storage protein reveals details of an unusual supersecondary structure.

Abstract: Scanning tunneling microscopy has been used to demonstrate that a spiral structure based on -reverse turns is adopted by the repeat sequences present in a group of wheat gluten proteins. This structure is smilar to the «spiral formed by a synthetic polypentapeptide based on a repeat sequence present in elastin. Wheat gluten and elastin are both elastomeric and it is possible that the spiral structure contributes to this property.Scanning tunneling microscopy (STM) and the derivative scanning probe techniques c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 18 publications
3
40
1
3
Order By: Relevance
“…The dry repetitive domain probably consists of a continuous series of these turns, which could organize into a so-called P-spiral, similar to that of elastin (Urry, 1993). The presence of this unusual supersecondary structure has been suggested previously from different studies (e.g., Tatham et al, 1984;Miles et al, 1991). Our hypothesis of the conversion of type I to type I1 p-turns is compatible with these observations.…”
Section: Structural Changes Upon Dryingsupporting
confidence: 80%
See 1 more Smart Citation
“…The dry repetitive domain probably consists of a continuous series of these turns, which could organize into a so-called P-spiral, similar to that of elastin (Urry, 1993). The presence of this unusual supersecondary structure has been suggested previously from different studies (e.g., Tatham et al, 1984;Miles et al, 1991). Our hypothesis of the conversion of type I to type I1 p-turns is compatible with these observations.…”
Section: Structural Changes Upon Dryingsupporting
confidence: 80%
“…Its structural organization may consist of a series of p-turns that organize in a @spiral structure (Tatham et al, 1984;Shewry et al, 1994); this idea is supported by scanning tunneling microscopy images of HMW Dx5 (Miles et al, 1991). The proposed &spiral structure for HMW proteins is similar to that of elastin, where it forms the basis for the molecule's elastic properties (Uny, 1993).…”
Section: Introductionmentioning
confidence: 65%
“…It has also been proposed that the β-turns are organized to give a regular spiral structure (termed a β-spiral) similar to that demonstrated for a synthetic polypentapeptide based on a repeat motif of elastin (Urry 1988). Molecular modelling can be used to generate such spiral structures (figure 4) whose dimensions (diameter, pitch and length) are consistent with those determined by viscometric analysis and revealed by STM of purified proteins in the hydrated solid state (Miles et al 1991). However, Kasarda et al (1994) have proposed that an alternative type of spiral structure is formed, based on γ-turns rather than β-turns.…”
Section: Structure Of the Hmm Subunit Repetitive Domainmentioning
confidence: 59%
“…Hydrodynamic studies indicated a rod-like structure in solution (Field et al 1987) and STM images showed that the central repetitive domains adopt a helical structure with a diameter of ca.1.9 nm and a pitch of ca. 1.5 nm in the hydrated solid state (Miles et al 1991). Thus, it has been proposed that the central repetitive domains form a β-spiral type structure.…”
Section: Structural Features Of Elastomeric Proteinsmentioning
confidence: 99%